Spiritual Resilience in Q.S. Al-Insyirah: A Reading of Al-Alusi’s Ruh al-Ma’ani through Reivich and Shatté’s Resilience Theory - Afriyan, Ricky; Isnaeni, Ahmad; Masruchin , Masruchin (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2026)
This article examines the concept of spiritual resilience in Q.S. Al-Insyirah through Imam al-Alusi’s Ruh al-Ma’ani and places it in dialogue with the resilience theory of Karen Reivich and Andrew Shatté. The study responds to the need for a more conceptually grounded reading of Q.S. Al-Insyirah that moves beyond motivational interpretations and considers its theological, psychological, and spiritual dimensions. Using a qualitative library research design, this study analyzes Al-Alusi’s interpretation of Q.S. Al-Insyirah through content analysis and the tahlili method, a verse-by-verse exegetical approach. The findings suggest that several key expressions in the chapter, including sharh al-sadr (expansion of the chest), the removal of burdens, ma‘a al-‘usr yusrā (with hardship comes ease), continued striving, and hope in God, may be read as interrelated elements of spiritual resilience. These elements resonate with selected dimensions of Reivich and Shatté’s theory, particularly emotional regulation, realistic optimism, self-efficacy, and reaching out. However, the relationship between the Qur’anic text and modern resilience theory should not be understood as exact equivalence, but as a dialogical and interpretive encounter. This study argues that Q.S. Al-Insyirah, as interpreted by Al-Alusi, offers a theological-transformative understanding of resilience, in which hardship becomes a site of inner expansion, divine reassurance, sustained effort, and spiritual reorientation. The article contributes to Qur’anic studies by showing how classical exegesis may enrich contemporary discussions of resilience without reducing Qur’anic meaning to modern psychological categories.